Auditory temporal acuity improves with age in the male mouse auditory thalamus: A role for perineuronal nets?. Issue 9 (27th September 2019) - Quraishe, Shmma; Newman, Tracey; Anderson, Lucy
Abstract: The ability to perceive and interpret environmental sound accurately is conserved across many species and is fundamental for understanding communication via vocalizations. Auditory acuity and temporally controlled neuronal firing underpin this ability. Deterioration in neuronal firing precision likely contributes to poorer hearing performance, yet the role of neural processing by key nuclei in the central auditory pathways is not fully understood. Here, we record from the auditory thalamus (medial geniculate body [MGB]) of young and middle‐aged, normally hearing male CBA/Ca mice. We report changes in temporal processing of auditory stimuli, with neurons recorded from ventral and medial MGB subdivisions of older animals more likely to synchronize to rapid temporally varying stimuli. MGB subdivisions also showed increased probability of neuronal firing and shorter response latencies to clicks in older animals. Histological investigation of neuronal extracellular specializations, perineuronal nets (PNNs) and axonal coats, in the MGB identified greater organization of PNNs around MGB neurons and the presence of axonal coats within older animals. This supports the observation that neural responses recorded from ventral and medial MGB of older mice were more likely to synchronize to temporally varying stimuli presented at faster repetition rates than those recorded from young adult animals. These changes are observed in animals with normal hearing thresholds, confirming that neural processing differs between the MGB subdivisions and such processing is associated with age‐related changes to PNNs. Understanding these age‐related changes and how they occur have important implications for the design of effective therapeutic interventions to improve speech intelligibility into later life. Abstract : Recordings made from ventral (v) and medial (m) MGB of middle‐aged, normally hearing, CBA/Ca male mice showed improved synchronization to rapidly varying stimuli. Increased precision was associated with localized expression of perineuronal net and axonal coats. This suggests the MGB retains significant capacity for anatomical and electrophysiological plasticity, maximizing efficiency into older age. Created in part with BioRender.com .